Skill Enhancement Through Training for Employees in the Commercial Printing Industry - Kute, Dattatraya Subhash; Upadhyay, Pooja (Prabandhan: Indian Journal of Management, 2016)
In the present scenario, employee training is considered as the source of gaining a competitive advantage. Employee training refers to the process of increasing the knowledge and skills of the workforce to enable them to perform their jobs more effectively. Skills enhancement is all about getting the skills you need to succeed at work. Skill enhancement is required in specific technical skills and essential skills. The technical skills and knowledge needed for work are changing all the time now, and therefore, everyone needs to be learning throughout their careers to stay relevant and competitive. The aim of this research was to study the enhancement of skills through training at different levels of employees in the commercial printing industry. The paper described and explored that training in any of these areas will help to develop skills that will enhance their effectiveness at different levels of employees in the commercial printing industry. The hypotheses were formulated to determine the association between training needs and enhancement of skills at different levels of employees in the commercial printing industry. Data was collected using questionnaires and interview. The research paper concluded that different levels of employee skills can be enhanced through training in the commercial printing industry.